(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2021)
The postpartum ovarian cyclicity which is associated with uterine involution has significant importance in fertility of sheep. The study was conducted to estimate the postpartum resumption of ovarian cyclicity in Lohi sheep during winter lambing season. Twelve pregnant ewes were selected. The commencement of ovarian cyclicity was investigated in postpartum ewes by estimating progesterone (P4) concentration in blood samples collected on weekly intervals starting from day of parturition till 12th week of postpartum. On the day of parturition, mean P4 concentration was 0.38 ± 0.08 ng / mL. After that, P4 level raised to 0.70 ± 0.13 and 0.83 ± 0.13 ng / mL during 1st and 2nd weeks respectively. During 3rd week, P4 concentration was 1.02 ± 0.18 ng / mL (ovulation). The peak P4 level during first estrous cycle was 3.02 ± 0.8 ng / mL and detected on 5th week. Second ovulation was observed during 6th week and again peak P4 concentration of 2nd cycle was found as 2.5 ± 0.64 ng / mL on 7th week. Based upon the hormonal profile, it was concluded that postpartum ovarian cyclicity resumed on 3rd week of postpartum in winter lambed Lohi sheep.